Analysis of Phytochemical Activity of Bougainvillea Spectabilis, Delonix Regia and Mussaenda Philippica Flowers (AYUSHDHARA, 2025)
Medicinal plants are additionally strong wellspring of naturally dynamic compound and offering expansive range of movement or activity. As a potent source of biologically active compounds, medicinal plants have long been an area of interest for effective chemotherapeutic agents because they offer a wide range of activities, with a focus on prevention. Therapeutic plants give various advantages to human wellbeing. Due to their natural origin and high therapeutic value, medicinal plants have gained more prominence. The purpose of this study was to determine whether Bougainvillea spectabilis (Paper Flower), Delonix regia (Gulmohar) and Mussaenda philippica (Bedina) contained phytochemicals. The phytoconstituents like alkaloids, glycosides, flavonoids, phenolics, quinones, phlobotannins, saponins, terpenoids and tannins were accounted for as the premise of restorative properties. Acetone, chloroform and water were used for the extraction purpose. Bougainvillea spectabilis is accounted for to have restorative qualities including anticancer, anti-hepatotoxic, anti-inflammatory, antimicrobial, antihyperlipidemic, antioxidant cancer prevention agent and antiulcer properties. Chronic fever, inflammation, antimicrobial constipation, arthritis, piles, hemoplagia, boils, scorpion bite, pyorrhea, bronchitis, dysmenorrhea and asthma are just a few of the conditions for which Delonix regia has been used. The different types of the class Mussaenda has numerous original phytochemical constituents which has high pharmacological exercises, for example, antioxidant, anti-inflammatory, antimicrobial and so on. Useful for treating numerous health disorders.